Prognostic role of dickkopf-1 in patients with cancer. Issue 21 (22nd May 2020) - Huang, Junfang; Lu, Tao; Kuang, Wenbing
Abstract : Abstract: As an antagonist for the WNT signal passway, dickkopf-1(DKK1) have a great important role in the occurence and development of various type cancer. The present paper performed a meta-analysis to evaluate the predictive significance of DKK1 in cancer. To assess the relationship between the expression of DKK1 and prognostic role in human cancers, a total of 16 articals were screened from the multiple online databases (Pubmed, EMBASE, CNKI, Web of Science and Google Scholar) in our study. By using the STATA soft, pooled hazard ratio and 95% confidence intervals of overall survival (OS), progression-free survival, disease-free survival and time to recurrence were used to evaluate the strength of this relationship. The meta-analysis showed that higher expression of DKK1 was significantly associated with shorter OS in cancer patients. In stratified analyzes, the higher expression of DKK1 could reduced the OS in patients with breast cancer, digestive system cancer and urogenital system cancer, but not patients with the lung cancer. It also showed that higher expression of DKK1 was significantly associated with shorter progression-free survival, disease-free survival and time to recurrence in cancer patients. The present study indicate that higher expression of DKK1 predict an unfavorable clinical outcome in patients with breast cancer, digestive system cancer and urogenital system cancer.